Abacavir Use and Risk for Myocardial Infarction and Coronary Artery Disease: Updated Meta-analysis of Data from Clinical Trials. (4th October 2017) - Nan, Cassandra; Shaefer, Mark S; Urbaityte, Rimgaile; Oyee, James; Hopking, Judy; Ragone, Leigh; McCoig, Cynthia; Vannappagari, Vani
Abstract: Background: Several observational studies and randomized controlled trials (RCTs) have suggested an association between abacavir (ABC) use and myocardial infarction (MI) but others, including meta-analyses of clinical trial data, have not. Methods: This updated meta-analysis estimates exposure-adjusted incidence rate (IR) and relative rate (RR) of MI and coronary artery disease (CAD) in subjects receiving ABC and non ABC-containing combination antiretroviral therapy (cART). Summary data from 52 Phase II-IV RCTs from a previous meta-analysis were combined with aggregate data from 14 new RCTs. Subjects were either randomized to ABC cART vs. other cARTs, or ABC was prescribed as a background medication. Primary analyses included ABC-randomized trials with a follow-up of ≥48 weeks and focused on MI. Secondary analyses included shorter duration trials and non-ABC-randomized trials and estimated IR and RR for both MI and CAD. Results: In 66 clinical trials (75% male, aged 18–85 years), 13, 119 adults were on ABC-containing cART and 7, 350 were not. Exposure-adjusted IR for MI was 1.5 per 1, 000 person-years (PY) [95% Confidence Interval (CI) 0.67–3.34] in the ABC-exposed group, and 2.18 per 1, 000 PY (95% CI 1.09–4.40) in the unexposed group with a RR of 0.69 (95% CI 0.24–1.98). RR for MI was 0.69 (95% CI 0.24–1.99) with inclusion of shorter duration studies, and 0.83 (95% CI 0.44–1.60) with inclusion of ABC non-randomized studies. The IR for CAD was 2.9 per 1, 000 PY (95% CI 2.09–4.02) in the ABC-exposed group and 4.69 per 1, 000 PY (95% CI 3.4–6.47) in the unexposed group with studies of ≥48 weeks of follow-up, with a RR of 0.62 (95% CI 0.39–0.98). With inclusion of studies of <48 weeks, IR for CAD in the ABC-exposed group was 2.96 per 1, 000 PY (95% CI 2.14–4.08) and 4.65 per 1, 000 PY (95% CI 3.37–6.42) in the unexposed group with a RR of 0.64 (95% CI 0.4–1.0) Conclusion: This expanded meta-analysis found comparable IRs for MI and CAD among ABC-exposed and unexposed subjects, suggesting no increased risk for MI or CAD following ABC exposure. These findings provide further evidence against an association between MI and CAD and ABC exposure in this clinical trial population. Modifiable risk factors for MI and CAD should be addressed when prescribing ART for treatment of HIV. Disclosures: C. Nan, GlaxoSmithKline: Employee and Shareholder, Salary. M. S. Shaefer, ViiV Healthcare: Employee and Shareholder, Salary. R. Urbaityte, GSK: Employee, Salary. J. Hopking, GlaxoSmithKline: Employee and Shareholder, Salary. L. Ragone, ViiV Healthcare: Consultant, Salary. C. McCoig, ViiV Healthcare: Employee, Salary. V. Vannappagari, ViiV Healthcare: Employee and Shareholder, Salary and Stocks